The take-action guide to world class learners book 1 how to make personalization and student autonomy happen - Zhao, Yong 1965-; Tavangar, Homa Sabet; McCarren, Emily; Rshaid, Gabriel F.; Tucker, Kay (Corwin, 2016)
Your blueprint to entrepreneur-minded schooling The Take-Action Guide to World Class Learners series provides the most complete information available on designing twenty-first century schools poised to leapfrog into the future! These practice-oriented books expand on Dr. Yong Zhao's acclaimedWorld Class Learners, which presents a new framework for cultivating creative and entrepreneurial students. Now, with this first book in the follow-up three-volume set, Zhao digs much deeper, revealing how exactly to put that framework into effect. This first book in the series provides specific strategies and practical advice on how to . Incorporate student choice for flexible, student-focused curriculum . Motivate students to turn strengths into passions . Cultivate students' technical, creative, decision making, and communication skills Implement Zhao's new paradigm shift one phase at a time, starting with Book 1. Better yet, read all three volumes for a complete blueprint to entrepreneur-minded schooling. "The ideal school should provide opportunities and resources to enable students to personalize their educational experiences instead of receiving a uniform standardized, externally prescribed, education diet." -Yong Zhao